TRANSLATIONAL MEDICINE: A NEW WAY FROM EXPERIMENTAL LABORATORY TO CLINICAL PRACTICE - Shadmanov, A.K.; Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The review article presents an analysis of modern problems in the development of medical science. The rationale for the need to develop a new direction in science - translational medicine, by creating conditions for the active transfer of the results of fundamental research to effective medical care is presented. To date, a colossal amount of information on molecular biology has been accumulated, subtle mechanisms of regulation of metabolic processes in the body, both under physiological and pathological conditions, have been revealed, and there are clear ideas on a number of pathologies, in particular, at the molecular and cellular levels. However, many aspects of such fundamental developments still remain at the level of theoretical material. The growing gap between understanding the causes of diseases and methods of their treatment is due to the fact that scientific developments and achievements are being introduced into practice for a long time or remain completely unclaimed in practical healthcare. The reason for this gap is related to the deepening specialization of theoretical researchers and experimenters, whose activities, with the amount of knowledge and time required for this, no longer allow them to combine scientific activity with medical practice. Translational medicine, as a young direction in medical science, is still at the level of its initial translational barrier, and the task is to introduce new biomedical scientific and theoretical provisions and methods to the field of clinical use as much as possible.